Gender disparities among adult recipients of layperson bystander cardiopulmonary resuscitation by location of cardiac arrest in Pan-Asian communities: A registry-based study. (February 2022) - Liu, Nan; Ning, Yilin; Ong, Marcus Eng Hock; Saffari, Seyed Ehsan; Ryu, Hyun Ho; Kajino, Kentaro; Lin, Chih-Hao; Karim, Sarah Abdul; Rao, G.V. Ramana; Ho, Andrew Fu Wah; Lim, Shir Lynn; Siddiqui, Fahad Javaid; et al.
Summary: Background: Bystander cardiopulmonary resuscitation (BCPR) is a critical component of the 'chain of survival' in reducing mortality among out-of-hospital cardiac arrest (OHCA) victims. Inconsistent findings on gender disparities among adult recipients of layperson BCPR have been reported in the literature. We aimed to fill this knowledge gap by investigating the extent of gender disparities in a cross-national setting within Pan-Asian communities. Methods: We utilised data collected from the Pan-Asian Resuscitation Outcomes Study (PAROS), an international, multicentre, prospective study conducted between 2009 and 2018. We included all OHCA cases with non-traumatic arrest aetiology transported by emergency medical services and excluded study sites that did not consistently collect information about the location of cardiac arrest. Logistic regression was used to analyse the association between gender and BCPR, stratified by location. Findings: We analysed a cohort of 56, 192 OHCA cases with an overall BCPR rate of 36.2% (20, 329/56, 192). At public locations, the BCPR rate was 31.2% (631/2022) for female and 36.4% (3235/8892) for male OHCA victims; while at home, the rate was 38.3% (6838/17, 842) for females and 35.1% (9625/27, 436) for males. Controlling for site differences and several factors in multivariable logistic regression, we found females less likely to receive BCPR than males in public locations (odds ratio [OR]=0.89, 95% confidence interval [CI]: 0.70–0.99), but more likely to receive BCPR at home (OR=1.16, 95% CI: 1.11–1.21). Interpretation: In Pan-Asian communities, gender differences exist in adult recipients of BCPR and differ between home and public locations. Future studies should account for additional information on bystanders and societal factors to identify targets for interventions. Funding: The study was supported by grants from the National Medical Research Council (NMRC/CSA/0049/2013) and Laerdal Foundation (20040).